An integrated electrode/separator with nitrogen and nickel functionalized carbon hybrids for advanced lithium/polysulfide batteries. (November 2016) - Fang, Ruopian; Zhao, Shiyong; Pei, Songfeng; Cheng, Yongxin; Hou, Pengxiang; Liu, Min; Cheng, Hui-Ming; Liu, Chang; Li, Feng
Abstract: Lithium-sulfur (Li-S) batteries are one of the most promising next-generation secondary battery systems for meeting increasing energy storage demands due to their high theoretical energy density. However, the commercialization of Li-S batteries is hindered by the low electrical conductivity of sulfur and the severe polysulfide shuttling problem. Here, we report the easy synthesis of a nitrogen-doped multi-functional nanocarbon hybrid decorated with nickel nanoparticles and its use in a conductive membrane for an integrated electrode/separator in Li/dissolved polysulfide batteries. The nitrogen-doping produces desirable polysulfide immobilization by enhanced adsorption and chemical bonding. The nickel nanoparticles act as electrocatalysts to accelerate the kinetics of sulfur conversion reactions. The assembled conductive membrane acts both as a conductive scaffold and a polysulfide adsorption layer that allows efficient charge transfer and effectively prevents polysulfide diffusion. Consequently, a Li/polysulfide cell with a high sulfur loading demonstrates excellent cycling stability with a low capacity decay rate of 0.115% per cycle over 200 cycles, showing great promise for use in advanced Li–S batteries. Graphical abstract: An integrated electrode/separator is designed for advanced Li/polysulfide batteries with the use of a nitrogen-doped multi-functional carbon hybrid decorated with nickel nanoparticles. Benefiting from the electron-donating nitrogen sites and nickel electrocatalysts, excellent cycling stability over 200 cycles with a low capacity decay rate of 0.115% per cycle is demonstrated by the Li/polysulfide cell with a high sulfur loading.